Spatiotemporal Planning of Construction Projects: A Literature Review and Assessment of the State of the Art - Ardila, Fabian; Francis, Adel (Frontiers in Built Environment, 2020)
Recently, new methods and technologies, including building information modeling (BIM) and lean management, have been introduced to the construction industry. Their objectives are to increase collaboration, ensure smooth flows of information, improve productivity, reduce different types of waste, and stabilize production. These constraints have forced the industry to gradually change by applying more adapted operational processes and contractual models that focus on value and by integrating the design, construction, and operation phases. Traditional scheduling methods based on activities modeling have become less adapted to this new reality. As a result, complementary concepts have emerged, particularly the Last Planner system, takt time, space planning, and spatiotemporal scheduling. This paper presents an extensive review and an assessment of the state of the art of the spatiotemporal planning of construction projects. The paper categorizes the research efforts, presents a timeline of the most significant scientific developments in this domain, and addresses their possible impacts on the construction industry.